2013
DOI: 10.1080/02786826.2013.794929
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Study on Aerodynamic Particle Resuspension from Monolayer and Multilayer Deposits on Linoleum Flooring and Galvanized Sheet Metal

Abstract: Resuspension is an important source of indoor particles and the amount of dust loading is an important factor in resuspension emission rates. Field studies have shown that light to heavy dust loads can be found in the indoor environment, on both the surfaces of flooring and ventilation ducts. These diverse particle deposits can be broadly classified as either a monolayer, in which particles are sparsely deposited on a surface, or a multilayer, in which particles are deposited on top of one another and there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
(77 reference statements)
2
22
1
Order By: Relevance
“…These findings are consistent with previously reported observation of increased fraction of released particles at higher surface loadings on hardwood and vinyl flooring . Other findings indicate that released fraction can either decrease, increase, or remain unchanged at higher surface dust loadings, contingent on the surface material and porosity, relative humidity, particle size and penetration, and deposit type . The scale of dust loadings used in our study is most likely to yield a less‐than monolayer deposit.…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent with previously reported observation of increased fraction of released particles at higher surface loadings on hardwood and vinyl flooring . Other findings indicate that released fraction can either decrease, increase, or remain unchanged at higher surface dust loadings, contingent on the surface material and porosity, relative humidity, particle size and penetration, and deposit type . The scale of dust loadings used in our study is most likely to yield a less‐than monolayer deposit.…”
Section: Resultssupporting
confidence: 92%
“…Boor et al. () conducted a wind tunnel study to investigate the effect of particle deposit structure on aerodynamic particle resuspension on flat surfaces. They found that particles were significantly easier (lower air velocity required) to resuspend from multilayer deposits than monolayer deposits.…”
Section: Resultsmentioning
confidence: 99%
“…129,130 Another common source of indoor particles is via mechanical processes, such as humans walking or air ow, which leads to the generation and/or resuspension of large particles such as dust, carpet bres, etc. 131,132 In the absence of in situ particle production, the major source of indoor particulate matter (PM) is inltration of outdoor aerosol particles through walls and windows. This leads to PM mass loadings being typically lower than those outdoors.…”
Section: Multiphase Processes (A) the Nature Of Indoor Surfaces And Amentioning
confidence: 99%